Reversible CO2 Capture by Conjugated Ionic Liquids through Dynamic Covalent Carbon–Oxygen Bonds. Issue 17 (26th July 2016) - Pan, Mingguang; Cao, Ningning; Lin, Wenjun; Luo, Xiaoyan; Chen, Kaihong; Che, Siying; Li, Haoran; Wang, Congmin
Abstract: The strong chemisorption of CO2 is always accompanied by a high absorption enthalpy, and traditional methods to reduce the absorption enthalpy lead to decreased CO2 capacities. Through the introduction of a large π‐conjugated structure into the anion, a dual‐tuning approach for the improvement of CO2 capture by anion‐functionalized ionic liquids (ILs) resulted in a high capacity of up to 0.96 mol CO 2   mol - 1 IL and excellent reversibility. The increased capacity and improved desorption were supported by quantum chemical calculations, spectroscopic investigations, and thermogravimetric analysis. The increased capacity may be a result of the strengthened dynamic covalent bonds in these π‐electron‐conjugated structures through anion aggregation upon the uptake of CO2, and the improved desorption originates from the charge dispersion of interaction sites through the large π‐electron delocalization. These results provide important insights into effective strategies for CO2 capture. Abstract : Dual‐tuning method : Through the introduction of a large π‐conjugated structure into the anion, a dual‐tuning approach to improve CO2 capture by anion‐functionalized ionic liquids (ILs) results in high capacities of up to 0.96  ; and excellent reversibility. Quantum chemical calculations, spectroscopic investigations, and thermogravimetric analysis indicate that the increased capacity is a result of stronger dynamic covalent bonds.